Problem of the freedom of the person in contemporary society - Матюхина, А. А. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2017)
The article examines the features of understanding of individual freedom and its place in human self-realization in modern society. The purpose of the article is implemented through successive consideration of the different approaches to the understanding of individual freedom – a value in itself and as a way of its realization.